Benzbromarone interferes with the interaction between Hsp90 and Aha1 by interacting with both of them - Yan Zhong; Li Shi; Zhuo Xu; Jing Gao; Qingyu Ma; Tianqi Gao; Junying Tang; Muya Xiong; Yechun Xu; Huixiong Dai; Hu Zhou; Naixia Zhang; et al. (Communications Biology)
Abstract Aha1 is one of the well-known co-chaperones of Hsp90. However, the action mode of Aha1 has not been fully elucidated yet, and the binding mode of Aha1’s C-terminal domain (Aha1-CTD) to Hsp90 is still under discussion. Meanwhile, since both Hsp90 and Aha1 contribute to tumorigenesis through controlling the homeostasis of onco-proteins, Hsp90-Aha1 system might serve as a target for anti-tumor drug development. A few of active compounds towards Hsp90-Aha1 system have been reported during the past years, but no compound binding pocket in Aha1 was pictured yet. Here in this manuscript, by using the discovered dual-modulator Benzbromarone as the probe, the pocket in Aha1 responsible for compound recognition is defined. Interestingly, as shown by the cryo-EM structures of Hsp90:Aha1 system, it is the same pocket that is involved in the in vitro interaction between Aha1-CTD and Hsp90-MD. Besides, Benzbromarone’s binding to Hsp90-NTD also exhibits unique structural features. Not surprisingly, due to the interference with the Hsp90 machinery, Benzbromarone could down-regulate the ATPase activity of the chaperone. Finally, according to the cellular-based experimental data, Benzbromarone has been shown to exhibit cytotoxicity against multiple cancer cell types, at least in part, through its modulation of the Hsp90 system.